Serum alkaline phosphatase levels and their association with neurological outcomes post-cardiac arrest - Wu-Jie Xia; Jing Song (BMC Cardiovascular Disorders)
Abstract Background Alkaline phosphatase (ALP) has been associated with an increased risk of cardiovascular events and is strongly correlated with adverse cerebrovascular outcomes. However, the relationship between ALP and neurological outcomes post-cardiac arrest (CA) remains underexplored. This study aims to investigate the association between serum ALP levels and 3-month neurological outcomes in patients who have experienced CA. Methods A retrospective review of 354 CA patients was conducted. Data for the study population were sourced from the DRYAD Digital Repository. Participants were categorized into three groups based on ALP level tertiles. Neurological outcomes were assessed at 3 months, with unfavorable neurological outcomes defined as a Cerebral Performance Categories (CPC) score of 3 to 5. Results After adjusting for covariates, elevated ALP levels were independently associated with an increased risk of unfavorable neurological outcomes post-CA (odds ratio = 1.095, 95%confidence interval: 1.021–1.174; P = 0.011). Compared to the low ALP tertile, the high ALP tertile exhibited a 1.54-fold increased risk of unfavorable neurological outcomes. Conclusion Elevated serum ALP levels were correlated with a higher risk of suboptimal neurological outcomes within 3 months following CA.